If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2(2x + 5) + 7 = 20 Reorder the terms: 3x + -2(5 + 2x) + 7 = 20 3x + (5 * -2 + 2x * -2) + 7 = 20 3x + (-10 + -4x) + 7 = 20 Reorder the terms: -10 + 7 + 3x + -4x = 20 Combine like terms: -10 + 7 = -3 -3 + 3x + -4x = 20 Combine like terms: 3x + -4x = -1x -3 + -1x = 20 Solving -3 + -1x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 20 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 20 + 3 -1x = 20 + 3 Combine like terms: 20 + 3 = 23 -1x = 23 Divide each side by '-1'. x = -23 Simplifying x = -23
| -2+4+7-5= | | 4(x+2)+15= | | 17x+5=14x+20 | | y=3x+17-1 | | 7x^2+-8+2=0 | | -(c-6)=-1 | | 7c-2(8c+11)=-1802 | | f(-2)=-7x+5x^2+10 | | x+0.05(12-x)=6.3 | | 5m^2-2=18 | | 5(2y-1)-(2y)=4 | | 9h+9=72 | | 14+3*t=-16 | | 4a^2+10=206 | | y=lnx^3 | | -1x^2+-2x+10=0 | | -7-9p^2=430 | | x(x+4)=4(x+16) | | 6x+4x-17=85-7x | | 9m-22=50 | | 10m+99= | | (3-9i)+(6-2i)=0 | | 4(-x-4)=20 | | 7-3x=5x-5 | | 4(3s+9)=168 | | 6(2k+1)-6k-2=14.016 | | 180-8x+2= | | 0=3/4x+3 | | -3n-6=15 | | 16x^2-2=79 | | 4(2l+1)=84 | | (6-2i)+(11+6i)=0 |